2012
DOI: 10.1039/c2jm33760f
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline indium sesquitelluride nanostructures: synthesis, growth mechanism and properties

Abstract: In the present work, we report for the first time the growth of uniform single crystalline In 2 Te 3 nanowires via the chemical vapor deposition (CVD) method. The CVD grown In 2 Te 3 nanowires are single crystals along [132] growth direction with a uniform diameter of around 150 nm and an average length of tens of microns. In addition, polycrystalline hierarchical nanostructures of In 2 Te 3 are also fabricated via a solvothermal method under low temperature conditions. The morphology and crystal structures ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…If large variations happen to the solution dielectric constant by alteration, or direct addition of high dielectric solvent, then dipolar, van der Waals and other attractions will be no more favorable for In 2 Te 3 crystal growth. 9 Low temperature and short duration of reaction time are also not favorable for completion of nanostructure growth. The When the reaction conditions provided enough activation energy for the growth of In 2 Te 3 nanostructures, then the most parts of Te nanorods were covered with scales, as shown in Fig.…”
Section: Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…If large variations happen to the solution dielectric constant by alteration, or direct addition of high dielectric solvent, then dipolar, van der Waals and other attractions will be no more favorable for In 2 Te 3 crystal growth. 9 Low temperature and short duration of reaction time are also not favorable for completion of nanostructure growth. The When the reaction conditions provided enough activation energy for the growth of In 2 Te 3 nanostructures, then the most parts of Te nanorods were covered with scales, as shown in Fig.…”
Section: Evolutionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] As one kind of telluride material, In 2 Te 3 is an important III-VI compound semiconductor with a narrow direct bandgap of 1.19 eV at room temperature and anti-uorite structure a-phase and zinc blend structure b-phase at low and high temperatures respectively. 9 Recently, we successfully synthesized crystalline In 2 Te 3 nanowires via a CVD method for the rst time and demonstrated crystalline In 2 Te 3 nanowires are promising candidates for application in high sensitivity and high-speed nanoscale photodetectors with broad band photoresponse. 10 However, no previous research has been reported on the synthesis and device application of In 2 Te 3 nanosheets.…”
Section: Introductionmentioning
confidence: 99%
“…Tellurium is a narrow band gap (E g = 0.34 eV), p-type elemental semiconductor with excellent potential applications such as in photoconductive, thermoelectric, catalytic, piezoelectric, chemical sensing and field emission devices [15][16][17]. Te nanostructures are also used as a template to synthesize different telluride based semiconductors [18][19][20]. Although there have been some reports on the growth mechanism of Te nanostructures [21][22][23][24], vertical, catalyst-free and epitaxial growth and re-growth mechanism of nanowires have not been reported due to the difficulties in controlling the synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Gold (Au) nanoparticles are often used as universal catalysts to define the growth of a 1D nanostructure, for example, high‐quality single‐crystalline GeTe nanowires12 and Sb 2 Te 3 13 nanobelts and nanotubes have been successfully synthesized by the Au‐catalyzed VLS growth mode. Recently, our group successfully synthesized In 2 Te 3 nanowires by an Au‐catalyst‐assisted growth process 22. The growth processes of In 2 Te 3 nanowire involve, first, the dissolution of gaseous In 2 Te 3 into the Au nanoparticles, followed by the nucleation of the wire and lateral growth.…”
Section: Synthesis Of Single‐crystalline Te‐based Nanostructuresmentioning
confidence: 99%